Use of unmanned aerial vehicles for monitoring of air pollution generated by stationary sources - Jirava, Pavel; Kuřík, Michal (SciTePress - Science and Technology Publications, 2017)
In the submitted paper, we focused on the use of unmanned aerial vehicles for the monitoring of air pollution by stationary sources. A quadrocope with digital image capture was used for experiments. The data thus obtained was preprocessed and the Ringelmann scale method for determining the darkness of the smoke plume was applied. This was used to decompose the acquired digital images onto their RGB components. The values obtained are relevant and can be used to determine the rate of air pollution by a stationary source. The advantage of this proposed procedure is to reduce the influence of the human factor on determining the darkness of the smoke and to eliminate the need for direct control of the stationary source of air pollution
Využití UAV pro monitoring znečištění ovzduší ze stacionárních zdrojů.
Keywords: UAV; stationary sources of air pollution; Ringelmann scale; data; smoke plume; UAV; stacionární zdroje znečištění; Ringelmannova škála; data; kouřová vlečka